Association of Physical Activity and Physical Education With Overweight and Obesity Among School-Aged Children and Adolescents in Pakistan: An Empirical Cross-Sectional Study - Moazzam Tanveer; Ejaz Asghar; Georgian Badicu; Nadeem Roy; Maximilian Siener; Umar Tanveer; Sameer Badri Al-Mhanna; Alexios Batrakoulis (Advances in Public Health)
Conclusion: This study underscores the critical need to enhance PA opportunities in schools and communities in Pakistan, particularly for girls, to address the rising rates of overweight and obesity.